Change Detection of Annual Temperature and Rainfall in Kalimpong Station under Hill Zone of West Bengal - Banerjee, Saon; Mukherjee, Asis; Sattar, Abdus; Biswas, Benukar (Indian Journal of Hill Farming, 2016)
Detecting the trend of temperature and rainfall change can help in assessing crop water availability, groundwater recharge and future climatic scenario. Considering the importance, the current paper aims at detecting the annual temperature and rainfall trend through Mann Kendall test and to evaluate the variation of Standardized Precipitation Index (SPI) values over years. The Mann Kendall test has been used to detect the climatological trend of the Kalimpong station, situated in the Hill zone of West Bengal. To determine the drought and wet situation over years, the Standardized Precipitation Index is used. The result reveals that the minimum temperature and rainfall show increasing trend and maximum temperature shows decreasing trend. The SPI values over years indicate that extremely wet and extremely dry weather condition occurs after 1980s. From this period the rainfall fluctuations also shows higher magnitude. The effect of global warming is present in the hill zone of West Bengal.